Analysis of the Honorary Council's Role in Enforcing Political Ethics in the Semarang City Regional House of Representatives (DPRD) for the 2024–2029 Period - Athaya Hanna Ayu Firdausyi; Wahyu Beny Mukti Setiyawan (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
Despite the presence of established ethical guidelines, disparities in ethical standards and their practical application persist among DPRD members, presenting an ongoing obstacle. This study examines the role of the Ethics Committee in enforcing the code of ethics in the Semarang City Council for the 2024-2029 period. The study aims to identify the Ethics Committee's efforts to improve effectiveness and to determine the supporting and inhibiting factors. The method used is a case study with a descriptive qualitative approach through field data collection. The results indicate that in its implementation, several violations related to political ethics are still found. This study provides an overview of the challenges faced by the Ethics Committee as the highest authority in the oversight mechanism to improve compliance with regulations among members of the Semarang City Council. Hopefully, the results of this study will serve as a basis for efforts to enhance the effectiveness of enforcing the code of ethics in the coming period.